Development of a Pulsar-Based Time-Scale - Hobbs, G.; Coles, W.; Manchester, R.; Keith, M.; Shannon, R.; Chen, D.; Bailes, M.; Bhat, Ramesh; Burke-Spolaor, S.; Champion, D.; Chaudhary, A.; Hotan, A.; et al. (Wiley-Blackwell Publishing Ltd., 2012)
Using observations of pulsars from the Parkes Pulsar Timing Array (PPTA) project we develop the first pulsar-based time-scale that has a precision comparable to the uncertainties in International Atomic Time-scales (TAI). Our ensemble of pulsars provides an Ensemble Pulsar Scale (EPS) analogous to the free atomic time-scale Échelle Atomique Libre. The EPS can be used to detect fluctuations in atomic time-scales and therefore can lead to a new realization of Terrestrial Time, TT(PPTA11). We successfully follow features known to affect the frequency of the TAI, and we find marginally significant differences between TT(PPTA11) and TT(BIPM11). We discuss the various phenomena that lead to a correlated signal in the pulsar timing residuals and therefore limit the stability of the pulsar time-scale.